Analisis Perubahan Laba Kotor Sebagai Alat Evaluasi Penyebab Naik Turunnya Laba Perusahaan - Heru Maruta (JAS (Jurnal Akuntansi Syariah), 2019)
This paper aims to provide information to the public about the understanding, uses, objectives, limitations and methods of calculating changes in gross profit analysis. Management requires information that can be used as a basis for evaluating the causes of the increase or decrease in the company's gross profit. By knowing the causes of the increase or decrease in the company's gross profit, management can determine the actions to be taken, if the gross profit shows an increase, then the factors causing it are worth defending. Conversely, if gross profit decreases, the factors that cause it are carried out as necessary so as not to be repeated in the next period. Analysis of changes in gross profit provides information that can be used by management as a basis for evaluation and actions needed in the next period, while to calculate the required data on sales and Cost of Goods Sold also in units and rupiah. The basis for calculating changes in gross profit is twofold, the first comparing the achievements of the current period with the previous and the second by comparing the target with the realization.